Identification of Bacterial Symbiont Sponge with Antibacterial Activity against Multi Drug Resistant Organism (MDRO) Bacteria from Sea Waters in Sibolga, North Sumatra Indonesia - Gultom, Endang Sulistyarini; Hasruddin, Hasruddin; Sitompul, Aida Fitriani; Situmorang, Albert D; Prasetya, Eko (Biosfer: Jurnal Tadris Biologi, 2021)
This research employed the experimental method with descriptive data analysis. It aimed to isolate and identify sponge symbiont bacteria with antibacterial potential against Multi-Drug Resistance Organisms (MDRO) with the 16S rRNA gene marker. Based on the study results, two sponges were obtained, namely Clathrina sp and Agelas sp, each having 11 and 7 isolates of symbiont bacteria, respectively. Based on the antibacterial activity test results, out of 18 isolates of symbiont bacteria, only 4 had antibacterial potential against MDRO (Klebsiella pneumoniae ESBL, Pseudomonas aeruginosa ESBL, or Staphylococcus lugdunensis MRSA) with inhibition zones of 9.3 mm, 8.3 mm, and 8.1 mm, respectively. The results of bacterial identification using the 16S rRNA gene sequence isolate S1I3, S1I9, and A1I3 belong to the Bacillus cereus and Bacillus paramycoides types. This research is expected to provide important information about sponge symbiont bacteria with antibacterial potential against MDRO.